On the Role of Heterogeneous Nanopore Junction in Osmotic Power Generation. Issue 5 (21st March 2019) - Li, Hao; Xiao, Feilong; Hong, Gang; Su, Jianjian; Li, Ning; Cao, Liuxuan; Wen, Qi; Guo, Wei
Summary of main observation and conclusion: Osmotic power generated by mixing ionic solutions of different concentration is an underutilized clean energy resource that satisfy potentially the ever‐growing energy demand. For decades, substantial efforts are made to enhance the power density. Toward this goal, we once developed a heterogeneous nanoporous membrane comprising of heterojunctions between negatively charged mesoporous carbon and positively charged macroporous alumina to harvest electric power from salinity difference and achieved outstanding performance ( J. Am. Chem. Soc .2014, 136, 12265). The heterogeneous nanopore junction effectively suppresses ion concentration polarization (ICP) at low concentration end, and consequently promotes the overall power density. However, to date, a systematic understanding of the role of the heterogeneous nanopore junction in osmotic energy conversion remains urgent and largely unexplored. Herein, we provide an in‐depth theoretical investigation on this issue with special emphasis on several influential factors, such as the ionic concentration, the surface charge density, and the geometry of heterogeneous part. To balance the suppression of ICP and maintenance of charge selectivity, we find that these influential factors in the heterogeneous part should be restricted to a specific range. These findings provide direct guidance for design and optimization of high‐performance nanofluidic power sources. Abstract : Ion concentration polarization can be effectively suppressed by heterogeneous nanopore junction at the low‐concentration end. With appropriately optimized parameters, the overall performance can be greatly enhanced.